Urban Dissensus: Spatial Self-Organisation at Wards Corner. - Vardy, Sam (Palgrave Macmillan, 2019)
Sam Vardy provides a London-based example-the Wards Corner Coalition-of how urban politics may play out very differently when urban inhabitants begin to think the political space of the urban in alternative ways. Drawing on the work of Ranciere and Lefebvre, he suggests that dissensus politics and spatial self-organisation are needed if the urban is to be politicised and thereby salvaged from the post-political grip of neoliberal consensus politics.
Keywords: Stadtforschung; Stadttheorie; Konflikt; Raum; Raumaneignung; Öffentlicher Raum; Sozialbewegung; Selbstorganisation; Hausbesetzung